Applicability and legal consequences of the criminal conciliation procedure - Shao, Huimin (Transactions on Social Science, Education and Humanities Research, 2024)
This paper provides insight into the use and impact of criminal reconciliation as an alternative form of criminal procedure in the modern justice system. By allowing the parties to reach an agreement through negotiation under the supervision of the judiciary, criminal conciliation aims to achieve a speedy resolution of criminal cases, reduce the burden on the courts and repair as much damage as possible to the victims. The article first describes the legal basis of criminal reconciliation and its development in different countries, demonstrating the diversity of this procedure and its adaptability across the globe. Subsequently, the article analyses in detail the conditions and procedures applicable to criminal reconciliation, highlighting the various factors that need to be taken into account in its practical operation, including the nature of the case, the will of the parties, and the possible legal consequences. Through case analyses, it reveals the advantages of criminal reconciliation in dealing with certain types of cases, such as the ability to resolve disputes quickly and reduce litigation costs and time. In addition, the article also discusses the limitations and potential risks of criminal settlements, such as the possibility of compromising the fulfilment of justice and the lack of necessary transparency and oversight in some cases. Finally, the article proposes a series of improvements to the criminal settlement process, including strengthening the oversight mechanisms of the process, ensuring the fairness of settlement agreements, and expanding public awareness and understanding of the process. Through comprehensive analyses and discussions, this article aims to provide legal professionals, scholars, and policymakers with a perspective for an in-depth understanding of criminal reconciliation, and to help them assess and improve existing judicial practices so that criminal reconciliation can not only enhance judicial efficiency, but also operate on the basis of ensuring fairness.